Analysis and Design of Enterprise Architecture at PT Pertamina EP Tarakan Field Company Using Togaf ADM 9.2 - Dzikyan, Muhammad; Setiadi, Farisya; Sutiyo, Sutiyo (Jurnal Locus Penelitian dan Pengabdian, 2025)
The industry is currently faced with challenges in managing massive data and operational complexity, including the oil and gas sector. Sustainable development is one of the main pillars for a company to survive in the era of technological change. Therefore, the implementation of enterprise architecture is very crucial for companies today, considering that this aligns with the Sustainable Development Goals (SDGs), especially Goal 9, which focuses on Industry, Innovation, and Infrastructure—driving economic growth through industries and quality development. The method used in this research is the approach of the TOGAF 9.2 framework in the design of enterprise architecture, with each phase including Preliminary Phase, Architecture Vision, Business Architecture, Information System Architecture, and Technology Architecture. The outputs produced in this research are artifacts in the form of design concepts and flowcharts for each phase of TOGAF ADM 9.2, including the oil and gas production process, the design of company data and applications, and the flow of technology use from the office to the drilling field location based on the current conditions applied.